A comparison of pediatric airway management techniques during out-of-hospital cardiac arrest using the CARES database. (November 2017) - Hansen, Matthew L.; Lin, Amber; Eriksson, Carl; Daya, Mohamud; McNally, Bryan; Fu, Rongwei; Yanez, David; Zive, Dana; Newgard, Craig
Abstract: Objective: To compare odds of survival to hospital discharge among pediatric out-of-hospital cardiac arrest (OHCA) patients receiving either bag-valve-mask ventilation (BVM), supraglottic airway (SGA) or endotracheal intubation (ETI), after adjusting for the propensity to receive a given airway intervention. Methods: Retrospective cohort study using the Cardiac Arrest Registry to Enhance Survival (CARES) database from January 1 201–December 31, 2015. The CARES registry includes data on cardiac arrests from 17 statewide registries and approximately 55 additional US cities. We included patients less than18 years of age who suffered a non-traumatic OHCA and received a resuscitation attempt by Emergency Medical Services (EMS). The key exposure was the airway management strategy (BVM, ETI, or SGA). The primary outcome was survival to hospital discharge. Results: Of the 3793 OHCA cases included from 405 EMS agencies, 1724 cases were analyzed after limiting the analysis to EMS agencies that used all 3 devices. Of the 1724, 781 (45.3%) were treated with BVM only, 727 (42.2%) ETI, and 215 (12.5%) SGA. Overall, 20.7% had ROSC and 10.9% survived to hospital discharge. After using a propensity score analysis, the odds ratio for survival to hospital discharge for ETI compared to BVM was 0.39 (95%CI 0.26–0.59) and for SGA compared to BVM was 0.32 (95% CI 0.12–0.84). These relationships were robust to the sensitivity analyses including complete case, EMS-agency matched, and age-stratified. Conclusions: BVM was associated with higher survival to hospital discharge compared to ETI and SGA. A large randomized clinical trial is needed to confirm these findings.